STUDY OF THE PROBLEM OF FORMATION PROFESSIONAL AND PEDAGOGICAL CULTURE FUTURE PRIMARY SCHOOL TEACHERS (Pedagogy of Higher and Secondary Education, 2022)
In clause it is shown growth of professional - pedagogical cultural of students and the future teachers of initial classes.